Глобальні розв'язки однієї двовимірної початково-крайової задачі для системи півлінійних рівнянь магнітопружності - Боценюк, О.М. (Український математичний журнал, 1996)
We prove the theorem on the existence and uniqueness of global solutions of a system of semilinear magnetoelasticity equations in a two-dimensional space.